Genetics and athletic performance - Cerit, M.; Dalip, M.; Yildirim, D. S. (Research in Physical Education, Sport and Health, 2020)
Sports Scientists and researchers in related disciplines unquestionably agreed on the fact that the level of physical development and process of adaptation to the exertions are due to the genetic makeup of individuals. Reasons such as lifestyle, environmental interactions and coming from different origins (ethnicity) by skin color are also facts that cannot be ignored in revealing the unique changes between people. The features encoded in DNA sequences or chains that cause changes between humans also determine the limits of physical performance. Therefore, the genetic characteristics of the Olympic athletes allow them to perform at a high level, more precisely to be slightly ahead of other competitors. The number of candidate genes associated with the potential for higher levels of physical exertion to occur is quite high. However, the number of genes that directly trigger athletic success among these candidate genes is also very limited. There are so many factors that affect athletic performance that even if one competitor is considered superior to another, the result is almost always doubtful. It is clear that ideal genes probably push an athlete to greatness, but that these ideal genes also do not guarantee an optimal result. The complexity of genetic and environmental influences on the physiological, motor and psychological characteristics also severely limits the scope of determining athletic abilities and generating a genetic profile of targeted success. Undoubtedly, athletes with a favorable genetic profile who interact with correct training practices are more likely to achieve higher performance levels. However, it is likely that the possible combinations of genetic and environmental factors that result in elite performance will remain enormous and often unpredictable.